2022
DOI: 10.1007/s40820-022-00869-7
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Electromagnetic Cooperative Network-Enhanced MXene/Ni Chains Aerogel-Based Microwave Absorber with Ultra-Low Matching Thickness

Abstract: Electromagnetic cooperative strategy has been presented as a mainstream approach that can effectively optimize the matching thickness of dielectric loss dominant system. However, it is still challenging for dielectric–magnetic loss coexisting-type absorber to develop electromagnetic wave (EMW) performance with ultra-low matching thickness (≤ 1 mm). Breaking the limitation of traditional electromagnetic response at microscopic/mesoscopic scale, a ficus microcarpa-like magnetic aerogel with macroscopical electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 58 publications
(52 reference statements)
1
43
0
Order By: Relevance
“…In recent years, lightweight aerogels with high porosity are considered as promising materials for EMI shielding [ 4 , 12 ]. Benefit to the three-dimensional (3D) porous structure of aerogel, the incident electromagnetic waves can be multiple reflected/scattered and lost in the porous structure, thus enhancing the EMI shielding performance, especially its electromagnetic wave absorption ability [ 13 , 14 ]. For instance, Zhao et al [ 15 ] reported transition-metal carbides (MXenes)/graphene oxide (GO) hybrid aerogel with aligned cellular microstructure and high conductivity (1085 S m −1 ), which effectively performs electron transfer and microwave attenuation exhibiting high EMI shielding effectiveness (EMI SE = 50 dB in the X band).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, lightweight aerogels with high porosity are considered as promising materials for EMI shielding [ 4 , 12 ]. Benefit to the three-dimensional (3D) porous structure of aerogel, the incident electromagnetic waves can be multiple reflected/scattered and lost in the porous structure, thus enhancing the EMI shielding performance, especially its electromagnetic wave absorption ability [ 13 , 14 ]. For instance, Zhao et al [ 15 ] reported transition-metal carbides (MXenes)/graphene oxide (GO) hybrid aerogel with aligned cellular microstructure and high conductivity (1085 S m −1 ), which effectively performs electron transfer and microwave attenuation exhibiting high EMI shielding effectiveness (EMI SE = 50 dB in the X band).…”
Section: Introductionmentioning
confidence: 99%
“…The RL value of EMW-absorbing materials can be calculated according to the generalized transmission line theory, and the formula is as follows , RL = 20 0.25em log 10 | Z in Z 0 Z in + Z 0 | Z normali normaln = Z 0 μ r ε r 0.25em tanh [ j true( 2 π italicfd c true) μ r ε r ] in which μ r and ε r are the permeability and complex permittivity, respectively; Z 0 represents the impedance of free space; Z in can be denoted as the input characteristic impedance; f is the given frequency; c is the light speed in vacuum; and d refers to the thickness of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The RL value of EMW-absorbing materials can be calculated according to the generalized transmission line theory, and the formula is as follows 21,38…”
Section: Microwave Absorption Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, EMW absorption materials include dielectric loss materials and magnetic loss materials. Dielectric loss materials have been of widespread concern in the past decades, such as graphene and its derivatives and MXenes. These kinds of materials have the merits of superior conduction property, high specific surface area, and multilayered structure. However, they have some shortages too.…”
Section: Introductionmentioning
confidence: 99%